Cryptocurrency and Money Laundering in Indonesian Criminal Law: A Doctrinal and Case-Based Analysis - Merly Markhamatul Izzah (Law and Judicial Review, 2026)
Objective: This study aims to analyze the application of the elements of the crime of money laundering, the construction of the perpetrator’s criminal liability, and to critically examine the judicial reasoning in District Court Decision No. 1240/Pid.Sus/PN.Tng involving the use of cryptocurrency. Research Design & Methods: This study employs a normative legal methodology through a literature review using legislative, conceptual, and case-based approaches, and is analyzed using descriptive qualitative methods based on primary, secondary, and tertiary legal sources. Findings: This study found that cryptocurrency has transformed money-laundering methods into more complex digital mechanisms, thereby complicating tracing and proof processes. Although there are no explicit regulations, the broad concept of “assets” in anti-money laundering law allows cryptocurrency to be treated as an asset for money laundering purposes. Courts have adopted an adaptive approach by interpreting crypto transactions as asset transfers and establishing criminal intent through circumstantial evidence, while maintaining the principles of actus reus and mens rea. Contributions: This study contributes to the development of legal discourse on cryptocurrency regulation within the anti-money laundering regime, particularly by highlighting interpretive practices in judicial decisions and identifying regulatory gaps in Indonesian law. Novelty: The novelty lies in integrating doctrinal legal analysis with a case-based examination of cryptocurrency-related money laundering, emphasizing judicial adaptation through functional equivalence and teleological interpretation within the existing legal framework.